Why does Waqf Literacy Matter? - Akbar, Nashr; Kassim, Salina (Global Review of Islamic Economics and Business, 2023)
Many studies have highlighted a low literacy level of waqf among Muslims all over the world. In Indonesia, an effort to measure the level of waqf literacy using an index was initiated by the Indonesian Waqf Board in 2020. The result has proven that there is a low level of waqf literacy in Indonesia. This study aims to explore the reasons behind the low level of waqf literacy and understand the importance of waqf literacy. Based on a literature survey, the following aspects need to be clearly explained and elaborated to effectively improve waqf literacy among the public. First, the unique characteristics of waqf compared to other Islamic alms; second, waqf literacy is positively related to waqf collection; third, the utilization of waqf can be further enhanced when the literacy is higher; and fourth, disputes and conflicts about waqf ownership are frequently due to lack of waqf literacy. In summary, this study is expected to increase the interest and attention of all stakeholders toward enhancing waqf literacy. Waqf authorities and waqf institutions are encouraged to intensify education and socialization about waqf, while researchers are expected to study more on waqf literacy. To further develop the waqf sector, it is necessary to have a road map to increase waqf literacy. Originality/Value: The study aims to explore the reasons behind the importance of waqf literacy in Indonesia. Identifying these reasons in the Indonesian context could pave the way for tailored interventions and policies to improve waqf literacy, which may have implications for similar contexts elsewhere.